2014
DOI: 10.15625/0866-7160/v36n1.4516
|View full text |Cite
|
Sign up to set email alerts
|

Genus Didymocarpus Wall. and a new record of species Didymocarpus purpureobracteatus Smith for the flora of Vietnam from Xuan Lien natural reserve, Thanh Hoa province

Abstract: Species Didymocarpus purpureobracteatus Smith is a new record for the flora of Vietnam. It was regarded as one endemic species to China, but up to now we have found it in Xuan Lien natural reserve (Thanh Hoa province). Voucher specimens were deposited in the Herbarium of the Institute of Ecology and Biological Resources, Hanoi, Vietnam (HN). This species is closed to D. poilanei but differs by bract elliptic or ovate, ca. 3-8 mm long; sepal tube ca. 8-9 mm long, sepal lobed ca. 2-3 mm long. So far, in Vietnam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Petrocosmea has more than 50 known species distributed in China, Vietnam, Thailand and India (Han et al 2018b); Didymocarpus has approximately 70 species range from northwest India, eastwards through Nepal, Bhutan, northeast India, Myanmar, to southern China, Vietnam, Laos, Cambodia, Thailand, the Malay Peninsula and northwards to Sumatra (Weber and Burtt 1998; Weber et al 2000; Möller et al 2016a; Hong et al 2018); Henckelia has 64 known species found in Sri Lanka, southern and north-eastern India, Nepal, Bhutan, southern China, northern Laos, northern Vietnam and northern Thailand (Weber et al 2011; Sirimongkol et al 2019). After thorough comparisons of diagnostic morphological, anatomical features and herbarium specimens available at BM, E, HITBC, K, KUN, NYBG and P with similar taxa of Petrocosmea , Didymocarpus , and Henckelia , and consulting the relevant literature for Petrocosmea (Wang 1985; Wang et al 1990, 1998; Burtt 1998a; Li and Wang 2004; Wei and Wen 2009; Gou et al 2010; Middleton and Triboun 2010; Zhao and Shui 2010; Shaw 2011; Xu et al 2011; Qiu and Liu 2015; Qiu et al 2011, 2012, 2015a, 2015b; Wang et al 2013; Zhang et al 2013; Han et al 2017, 2018a, 2018b), Didymocarpus (Wang et al 1998; Burtt 1998b, 1999, 2001; Weber et al 2000; Hilliard 2001; Li and Wang 2004; Nangngam and Maxwell 2013; Wen et al 2013; Li and Li 2014; Nangngam and Middleton 2014; Phuong et al 2014; Li and Wang 2015; Cai et al 2016; Joe et al 2016; Hong et al 2018), and Henckelia (Wang et al 1998; Weber and Burtt 1998; Burtt 2001; Weber et al 2011; Middleton et al 2010; Ranasinghe et al 2016; Sirimongkol et al 2019) from China and adjacent regions, it was confirmed that the four specie...…”
Section: Introductionmentioning
confidence: 99%
“…Petrocosmea has more than 50 known species distributed in China, Vietnam, Thailand and India (Han et al 2018b); Didymocarpus has approximately 70 species range from northwest India, eastwards through Nepal, Bhutan, northeast India, Myanmar, to southern China, Vietnam, Laos, Cambodia, Thailand, the Malay Peninsula and northwards to Sumatra (Weber and Burtt 1998; Weber et al 2000; Möller et al 2016a; Hong et al 2018); Henckelia has 64 known species found in Sri Lanka, southern and north-eastern India, Nepal, Bhutan, southern China, northern Laos, northern Vietnam and northern Thailand (Weber et al 2011; Sirimongkol et al 2019). After thorough comparisons of diagnostic morphological, anatomical features and herbarium specimens available at BM, E, HITBC, K, KUN, NYBG and P with similar taxa of Petrocosmea , Didymocarpus , and Henckelia , and consulting the relevant literature for Petrocosmea (Wang 1985; Wang et al 1990, 1998; Burtt 1998a; Li and Wang 2004; Wei and Wen 2009; Gou et al 2010; Middleton and Triboun 2010; Zhao and Shui 2010; Shaw 2011; Xu et al 2011; Qiu and Liu 2015; Qiu et al 2011, 2012, 2015a, 2015b; Wang et al 2013; Zhang et al 2013; Han et al 2017, 2018a, 2018b), Didymocarpus (Wang et al 1998; Burtt 1998b, 1999, 2001; Weber et al 2000; Hilliard 2001; Li and Wang 2004; Nangngam and Maxwell 2013; Wen et al 2013; Li and Li 2014; Nangngam and Middleton 2014; Phuong et al 2014; Li and Wang 2015; Cai et al 2016; Joe et al 2016; Hong et al 2018), and Henckelia (Wang et al 1998; Weber and Burtt 1998; Burtt 2001; Weber et al 2011; Middleton et al 2010; Ranasinghe et al 2016; Sirimongkol et al 2019) from China and adjacent regions, it was confirmed that the four specie...…”
Section: Introductionmentioning
confidence: 99%